印尼疫情期间及恢复实体课后的华文教学现状 - Symphony Akelba Christian (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2022)
摘要由于新冠疫情的关系，自2020年3月起，印尼的华文教学被迫进行线上课。印尼华文教师们不得不要适应这一新的教学模式。随着疫情好转，教师和学生也顺利接种疫苗后，印尼开始恢复实体课，教师也要再次回到实体课的教学模式。本研究主要研究印尼疫情期间和恢复实体课后的华文教学现状。主要是通过两份调查问卷收集研究资料。参与本次调查的印尼华文教师共有131名。研究结果显示，疫情期间大部分的华文教学是通过Zoom和Google Meet这两个平台进行同步的线上教学。教师们的数字技术能力也有很大的提高，除了准备PPT课件，教师们也使用网上的资源和线上软件/网站/工具来进行线上练习、作业和考试，成功吸引了学生的注意力并提高了学生的学习兴趣。恢复实体课后，部分教师也还继续使用这些软件和技术，以便不断提高教学质量。由此可见，技术在华文教学中的应用是未来印尼华文教学的发展趋势。 关键词: 线上教学；实体课；华文。 AbstractDue to the COVID-19 outbreak, since March 2020, Chinese language teaching in Indonesia has been forced to conduct online classes. Indonesian Chinese teachers have to adapt to this new teaching model. After the improvement of the new crown epidemic, after teachers and students successfully received the vaccine, Indonesia will resume face-to-face learning, and teachers will also return to the teaching mode of face-to-face learning again. This study mainly studies the current situation of Chinese language teaching in Indonesia during the epidemic and after the resumption of face-to-face learning. The research data was mainly collected through two questionnaires. A total of 131 Indonesian Chinese teachers participated in this survey. The research results show that during the epidemic, most of the Chinese teaching was conducted online through two teaching platforms, Zoom and Google Meet. Teachers' digital competence have also been greatly improved. In addition to preparing PPT courseware, teachers also use online resources and online software/websites/tools to conduct online exercises, assignments and exams, successfully attracting students' attention and improving students interest in learning Chinese. After the resumption of face-to-face learning, some teachers continue to use these technologies to continuously improve the quality of teaching. It can be seen that the application of technology in Chinese language teaching is the development trend of Chinese language teaching in Indonesia in the future. Keywords: Online learning; face-to-face learning; Chinese.